Low-cost electronic bamboo walking stick: an innovative assistive mobility aid for the blind - Elisha D. Markus; Frank Kulor; Michael W. Apprey; Kafui T. Agbevanu (Universitas Ahmad Dahlan, 2022)
Present-day advancements in embedded systems have uncovered a wide area of innovation in inexpensive supportive systems for the visually impaired. Right from the uncomplicated white cane up to the most exceptional electronic walking stick, many designs have been proposed aiming at assisting and protecting visually challenged persons. This paper aims at contributing to these assistive aids by designing a bamboo stick sensor-based unit with ultrasonic and water detection sensors which is robust, cheap, and easily operated for the deprived blind person. Thus, improving the usefulness of the current white stick to consolidate both above-knee and below-knee deterrent identifications. The developed bamboo stick simply operates using ultrasound sensors for sensing the impediments before contact and a water detection sensor for water detection on the pathway. It offers vibration and different sound feedbacks to the operator per the spot of the obstacle. The results obtained by trial from a volunteer who walked an obstructed path blindfolded were excellent. The results ensure quick detection, safety and enhance the speed of mobility of the user. The simulations performed were accurate and relevant to the ultimate goal of the paper. The electronic bamboo walking stick developed can be used to guide the visually impaired in an indoor or outdoor environment.